Preventive bilateral femoral nailing in atypical femoral fracture non responder to anabolic therapy: case report and mini-review - Neri, Elisabetta; Gabriele, Livia; Bottai, Vanna; Andreani, Lorenzo; Bonicoli, Enrico; Scaglione, Michelangelo (Acta Biomedica Atenei Parmensis, 2022)
Currently bisphosphonates are the main antiresorptive medications used in osteoporosis. However, a prolonged use of these drugs is associated to an increased risk of atypical femoral fractures, especially in patients suffering from others predisposing clinical conditions.This report describes a case of a woman presenting bilateral impending femoral fracture initially treated with bisphosphonates suspension and intramedullary nailing of right femur. Despite anabolic therapy, the patient presented progression of incomplete contralateral femoral fracture which required a second surgical treatment.